2004
DOI: 10.1016/j.molcel.2004.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Mastermind Recruits CycC:CDK8 to Phosphorylate the Notch ICD and Coordinate Activation with Turnover

Abstract: Notch signaling releases the Notch receptor intracellular domain (ICD), which complexes with CBF1 and Mastermind (MAM) to activate responsive genes. We previously reported that MAM interacts with CBP/p300 and promotes hyperphosphorylation and degradation of the Notch ICD in vivo. Here we show that CycC:CDK8 and CycT1:CDK9/P-TEFb are recruited with Notch and associated coactivators (MAM, SKIP) to the HES1 promoter in signaling cells. MAM interacts directly with CDK8 and can cause it to localize to subnuclear fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
555
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(595 citation statements)
references
References 46 publications
29
555
2
4
Order By: Relevance
“…The Jones group has shown that Mastermind recruits CyclinC/Cdk8, which is part of the repressive Mediator complex [71]. This Cyclin/Cdk pair strongly enhances NICD phosphorylation and PEST-dependent degradation after ubiquitinylation by the Fbw7/ Sel10 ubiquitin ligase (Fig.…”
Section: Cyclinc/cdk8 and Phosphorylation Of Notch Receptormentioning
confidence: 97%
See 1 more Smart Citation
“…The Jones group has shown that Mastermind recruits CyclinC/Cdk8, which is part of the repressive Mediator complex [71]. This Cyclin/Cdk pair strongly enhances NICD phosphorylation and PEST-dependent degradation after ubiquitinylation by the Fbw7/ Sel10 ubiquitin ligase (Fig.…”
Section: Cyclinc/cdk8 and Phosphorylation Of Notch Receptormentioning
confidence: 97%
“…This implies that SKIP is part of both RBP transcriptional repression and activation complexes. However chromatin immunoprecipitation experiments from the Jones group suggest that SKIP is only recruited to the promoter when Notch is present [71].…”
Section: Epigenetic Regulation Of Notch Target Genesmentioning
confidence: 99%
“…31 These opposite effects can affect tissue-specific transactivators differently. CDK8 is known to directly regulate the activities of several transcription factors in metazoans, including p53, E2F1, ÎČ-catenin, SMADs and Notch intracellular domain (N ICD ), 6,16,17,36,[48][49][50] all of which are commonly dysregulated in a wide variety of human cancers. We recently showed that CDK8 inhibits lipogenesis by directly phosphorylating SREBP and promoting the degradation of SREBP in Drosophila and mammalian cells.…”
Section: Overexpression Of Cdk8 Inhibits Growth Of Human Endometrial mentioning
confidence: 99%
“…31 Interestingly, CDK8-dependent phosphorylation positively regulates the activity of p53 and SMADs but negatively regulates the activity of E2F1, N ICD and SREBP. 6,16,17,31,36,[48][49][50] Thus, it is reasonable to postulate that CDK8 amplification or mutation can differentially affect these transactivators in a tissue-specific or biological context-specific manner, which may explain why CDK8 amplification or mutation can be oncogenic or tumor-suppressive in different tissues. Clearly, either gain or loss of CDK8 can contribute to tumorigenesis, and it would be an oversimplification to designate CDK8 as either an oncoprotein or a tumor suppressor.…”
Section: Overexpression Of Cdk8 Inhibits Growth Of Human Endometrial mentioning
confidence: 99%
“…Therefore, unknown proteins that interact with TAD2 likely are required for Notch target gene activation. A protein that interacts directly with MAML1 is CDK8 that can cause ICN1 phosphorylation and degradation (Fryer et al, 2004). The exact binding site was not mapped, but neither MAML1 mutant with deletion aa 75-300 nor 1-301 binds to CDK8.…”
Section: Identification Of Maml Proteins and Investigations Into Theimentioning
confidence: 99%